FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MP-ASI PADA BAYI 0-6 BULAN DI WILAYAH KERJA PUSKESMAS AIR DINGIN TAHUN 2024 - Karlina, Novvi; Mutia Ulfa, Rahmi; Yanti Sitorus, Nopita (Ensiklopedia Research and Community Service Review, 2025)
Complementary foods for breast milk (MP-ASI) are additional foods that are given when the baby is 6 months old and is only a companion, because breast milk is the main food. In the city of Padang, the lowest coverage of exclusive breastfeeding has not reached 80%, namely the Cold Water Health Center, which is 52.57%. The purpose of the study is to find out the factors related to the feeding of complementary breastfeeding to infants 0-6 months at the Cold Water Health Center in 2024. This study is   analytical with a cross sectional design. This research was conducted on August 10-22, 2024. The population is 197 people, the sampling method  is Simple Random Sampling. Secondary data collection and primary data, the data were analyzed using univariate and bivariate analysis and then tested with Chi-Square statistics.The results of the study can be seen that the respondents have a low level of knowledge (34%), negative attitudes (49%), negative socio-culture (42.6%), and MP-ASI (61.7%). The results of the statistical test using the Chi-Square  test showed that there was a meaningful relationship between the level of knowledge and the provision of MP-ASI (p=0.001), there was a meaningful relationship between attitude and the provision of MP-ASI (p=0.001), and there was a meaningful relationship between socio-culture and the provision of MP-ASI (p=0.000) at the Cold Water Health Center in 2024.The results of the study can be concluded that the level of knowledge possessed by the respondents is still low, negative attitudes, negative socio-culture and MP-ASI are still high. For this reason, it is hoped that the Puskesmas can increase socialization to the community through posyandu activities about MP-ASI for babies, especially the selection of MP-ASI types and sources of nutrients in food. Keywords   : Level of Knowledge, Attitude, Socio-Culture, Complementary Breastfeeding